Vidales, Vallejo, Vanguardia - Henao Durán, Juan Carlos; Tobón Giraldo, Daniel Jerónimo (Estudios de Literatura Colombiana, 2011)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]--> Resumen: El colombiano Luis Vidales y el peruano César Vallejo se cuentan entre los máximos exponentes de la vanguardia literaria de sus países. El artículo indaga, a través de distintas nociones del concepto vanguardia y a través del análisis de dos poemas, hasta qué punto es válida esta afirmación general. Descriptores: Vidales, Luis; Poesía colombiana; Vallejo, César; Poesía peruana; Vanguardia. Abstract: Luis Vidales and César Vallejo, both writers from Colombia and Peru respectively, are considered the most important representatives of the vanguard literature of their countries. The article goes deep into the rightness of this general affirmation by taking into account different acceptations of the concept vanguardism and analyzing a poem from each of them. Key words: Vidales, Luis; Colombian poetry; Vallejo, César; Peruvian poetry; Vanguardism.